REPRESENTASI KELUGASAN BERANDA LAMAN WWW.COVID19.GO.ID: TINJAUAN ANALISIS WACANA KRITIS - Suswandi, Irwan (MIMESIS, 2020)
The digital era has encourages information providers to innovate by utilizing the internet to convey information quickly. No exception for the government in a way to provide information and news related to Covid-19 which has become a global pandemic. Using a website as a source of information can give quick access for people to obtain actual and valid information relating to Covid-19. Through www.covid19.go.id, the government provides a facility for people to be able to access all information about Covid-19 matters. In this research, the researcher will analyze how government gives simplicity in providing information related to Covid-19, which is represented on the www.covid19.go.id homepage. The researcher used CDA (critical discourse analysis) theory from Fairclough to analyze the text found on the www.covid19.go.id homepage. Then, the results of critical discourse analysis were linked with the reputation theory of Charles J. Fombrun. The analysis produced information in the form of language units of www.covid19.go.id homepage which contains a simplicity matter in the delivery of information. From this analysis, the researcher can conclude that the simplicity in www.covid19.go.id homepage was represented through the website components, content, and propositions contained in the homepage. The simplicity matter also found in the use of modes, those were descriptive, persuasive, and interrogative mode.